2004
DOI: 10.1103/physrevd.70.034019
|View full text |Cite
|
Sign up to set email alerts
|

Tetracritical behavior in strongly interacting theories

Abstract: We suggest a tetracritical fixed point to naturally occur in strongly interacting theories. As a fundamental example we analyze the temperature--quark chemical potential phase diagram of QCD with fermions in the adjoint representation of the gauge group (i.e. adjoint QCD). Here we show that such a non trivial multicritical point exists and is due to the interplay between the spontaneous breaking of a global U(1) symmetry and the center group symmetry associated to confinement. Our results demonstrate that taki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…This is so since in these models the sign problem is absent. An initial study of the nonzero matter density and temperature phase diagram, highly relevant for the new dark matter candidates, has been presented in [25]. Here it was also shown that there is an intriguing relation between the matter density driven chiral phase transition and the deconfining one yielding a very rich phase diagram as function of the temperature and matter density.…”
Section: Extreme Technicolormentioning
confidence: 87%
“…This is so since in these models the sign problem is absent. An initial study of the nonzero matter density and temperature phase diagram, highly relevant for the new dark matter candidates, has been presented in [25]. Here it was also shown that there is an intriguing relation between the matter density driven chiral phase transition and the deconfining one yielding a very rich phase diagram as function of the temperature and matter density.…”
Section: Extreme Technicolormentioning
confidence: 87%
“…The linearly realized one will permit us to study immediately the thermal properties of the chiral phase transition relevant for electroweak baryogenesis as done for the case of Minimal Walking Technicolor [21]. Due to the interplay between multiple nearby phase transitions [60,61] we expect novel phenomena of direct interest for cosmological applications. The linearly realized Lagrangian, once extended to contain also the spin one composite spectrum, will be of immediate interest for LHC phenomenology.…”
Section: Discussionmentioning
confidence: 99%
“…In particular in two-color adjoint QCD deconfinement is a second-order transition and we expect a tetracritical point in the phase diagram where the deconfinement and BEC transition lines intersect [10]. In three-color adjoint QCD deconfinement is a first-order transition so that the tetracritical point is replaced with two nearby tricritical points where the second-order BEC line meets the firstorder deconfinement line [2].…”
Section: Adjoint Qcdmentioning
confidence: 96%